Epidemiological aspects of leptospirosis in Rio Grande do Sul during the 2024 Flood - Renan Konig Leal; Millena Fernandes; Caroline Pereira Vieira; Ester Cristina Corrêa da Rocha; Nícolas Firmiano Flores; Wellyngton Vieira Eufrazio; Carolina Zomer da Silva; Betine Pinto Moehlecke Iser; Josiane Somariva Prophiro (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Background: Leptospirosis is a serious zoonosis. In 2024, Rio Grande do Sul (RS) experienced floods affecting 93% of the municipalities and 8.8% of the population. In this study, we reviewed the leptospirosis notifications post-flooding. Methods: Descriptive quantitative study using secondary data from the RS Health Department Epidemiological Report. Results: A total of 7,129 suspected cases were reported, of which 788 were confirmed. Porto Alegre had the highest number of cases and Travesseiro had the highest incidence rate. Epidemiological weeks 20-24 peaked in cases and deaths (47 total cases), with significant municipal variation. Conclusions: The 2024 floods caused a significant increase in leptospirosis, underscoring the need for a One Health approach and strengthening public health policies.